SUR1-E1506K mutation impairs glucose tolerance and promotes vulnerable atherosclerotic plaque phenotype in hypercholesterolemic mice - Erika Gurzeler (Public Library of Science (PLoS), 2021)
Background and aims Diabetes is a major risk factor of atherosclerosis and its complications. The loss-of-function mutation E1506K in the sulfonylurea receptor 1 (SUR1-E1506K) induces hyperinsulinemia in infancy, leading to impaired glucose tolerance and increased risk of type 2 diabetes. In this study, we investigate the effect of SUR1-E1506K mutation on atherogenesis in hypercholesterolemic LDLR-/- mice. Methods SUR1-E1506K mutated mice were cross-bred with LDLR-/- mice (SUR1Δ/LDLR-/-), 6 months old mice were fed a western-diet (WD) for 6 months to induce advanced atherosclerotic plaques. At the age of 12 months, atherosclerosis and plaque morphology were analyzed and mRNA gene expression were measured from aortic sections and macrophages. Glucose metabolism was characterized before and after WD. Results were compared to age-matched LDLR-/- mice. Results Advanced atherosclerotic plaques did not differ in size between the two strains. However, in SUR1Δ/LDLR-/- mice, plaque necrotic area was increased and smooth muscle cell number was reduced, resulting in higher plaque vulnerability index in SUR1Δ/LDLR-/- mice compared to LDLR-/- mice. SUR1Δ/LDLR-/- mice exhibited impaired glucose tolerance and elevated fasting glucose after WD. The positive staining area of IL-1β and NLRP3 inflammasome were increased in aortic sections in SUR1Δ/LDLR-/- mice compared to LDLR-/- mice, and IL-18 plasma level was elevated in SUR1Δ/LDLR-/- mice. Finally, the mRNA expression of IL-1β and IL-18 were increased in SUR1Δ/LDLR-/- bone marrow derived macrophages in comparison to LDLR-/- macrophages in response to LPS. Conclusions SUR1-E1506K mutation impairs glucose tolerance and increases arterial inflammation, which promotes a vulnerable atherosclerotic plaque phenotype in LDLR-/- mice.